Anti-Corruption Education Relationship With an understanding of the values of the honesty of students At SDIT Al Manar Purwakarta - Maryam Djabarudin; Manpan Drajat; Saepul Mukti; Usep Setiawan (Qoumun: Jurnal Pengabdian Masyarakat, 2025)
This research is motivated by the behavior of students who lack understanding of anti -corruption education and the lack of understanding of the values ​​of honesty, so that acts appear less commendable than students such as dishonesty, rounding of fellow friends, and lack of discipline of school rules. This study aims to describe the relationship between anti -corruption education with understanding the value of honesty at SDIT Al Manar Purwakarta. This is important to be examined considering how many cases of corruption in Indonesia that are increasingly widespread in almost all the environmental orders of the community, especially education. The method used in this study is quantitative experimental fund sampling with homogeneous data which is used as a sample of the entire population of 65 students. The theoretical analysis used for anti-corruption education variables (X) is a gone theory, while the variable understanding of honesty (Y) uses the theory of Roger. Based on the results of data analysis, it was concluded that first, the understanding of the values ​​of students' pretest in the control class was considered good with an average score of 70% and understanding the value of students in the pretest class in the experimental class was considered good with an average value of 78%. Second, understanding the value of honesty in the experimental class when pretest is considered very good with an average value of 88%. It is concluded that there is a positive and significant influence between anti -corruption education and understanding the values ​​of students' honesty. There is a significant difference regarding the understanding of students' honesty values ​​after treatment between the control class and the experimental class. Based on these data it is concluded that t count 0.0192> t table 0.05 which means there is a significant difference.